Crack-bridging degradation and evolution in SFRC structural beams under variable amplitude flexural cyclic loading. (15th September 2021) - Adel, Mohamed; Matsumoto, Koji; Nagai, Kohei
Abstract: A few studies have demonstrated a degradation in the performance of the steel-fibers in bridging cracks over the lifetime of steel-fiber reinforced concrete (SFRC) structures but only considered for constant amplitude cyclic loading. However, SFRC structures in practice are subjected to variable amplitude loading, thus their crack-bridging would be influenced by the preceding loading history. This concern has so far remained unexplored. This study presents experimental and analytical flexural cyclic responses of SFRC structural beams under constant and variable amplitudes. The crack-bridging stresses are evaluated using a proposed inverse method based on sectional analysis calculations. Besides, the maximum rebar strain level is correlated with the crack-bridging degradation law, aiming at reflecting the beam's macroscopic response. The results show that crack-bridging stress increases if the fatigue load level increases, indicating that new fibers play a role in bridging cracks along the crack length. Further, decreasing the fatigue load level leads to an instant decrease in crack-bridging, which is followed by a stabilization as the pullout stress applied to the bridging fibers is reduced. Finally, a diagram of crack-bridging degradation and evolution is proposed regarding the maximum rebar strain, which is supposed to be a valuable tool in the SFRC structural design.